(untitled) (European Journal of Emerging Technology and Discoveries, 2025)
This article is devoted to measures for the implementation of preventive interviews conducted by preventive inspectors with objects of crime prevention. The article comprehensively covers the theoretical and practical foundations of preventive interviews, psychological and sociological aspects, possibilities of using modern digital technologies, and ways to increase the effectiveness of these interviews. Preventive interviews serve to prevent crimes, increase the legal literacy and social responsibility of citizens, as well as strengthen the rule of law in society. The article emphasizes the importance of an individual approach, constructive communication methods, analysis of the social environment, the use of artificial intelligence and other modern tools, as well as cooperation with state and non-state organizations. The activities of preventive inspectors occupy an important place in the law enforcement system and serve to ensure security and stability in society. The article can serve as an important resource for lawyers, sociologists, psychologists, and specialists engaged in preventive activities.